Restructuring Pakistan: a global imperative - Saighal, Vinod (New Delhi, 2002)
In a bold departure from conventional thinking on the subject, the author presents an exciting blueprint for the Resurgence of Pakistan from a terrorism sponsoring state to a dynamic and responsible member of the comity of nations. In a veritable tour de force he demonstrates that fundamentalism' has a limited life span. He goes on to say that if fundamentalism is not given up it will self destruct the polity that adheres to it. The new global currents linked to the spread of knowledge, thanks to the information revolution, will take care of that, says the author who has dealt with several other issues ranging from the nuclear issue to the interplay of global forces in South and Central Asia.
Keywords: Global terrorism-Pakistan